2020
DOI: 10.3390/su12114345
|View full text |Cite
|
Sign up to set email alerts
|

Potential Early Adopters of Hybrid and Electric Vehicles in Spain—Towards a Customer Profile

Abstract: The adoption of electric vehicles (EVs) by consumers is regarded as a key strategic goal for the reduction in transport-related air pollution levels. Although sales of EVs continue to rise year on year, generally, the attainment of the strategic goals set by various governments for the adoption of EVs remains a distant target. The purpose of this study is to identify the customer profile of early adopters of EVs in Spain: one of Europe’s largest economies, yet the country with the lowest uptake of EVs at prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 82 publications
(142 reference statements)
0
16
0
Order By: Relevance
“…Although previous studies have analysed the relevance of demographic characteristics of prospective buyers of EVs [10,11,33], the findings of this literature are far from unanimous. Previous studies assert that demographic factors have a positive impact on both pro-environmental behaviour (e.g., [12,54] and in product innovation adoption [55].…”
Section: New Mobility Trendmentioning
confidence: 98%
See 3 more Smart Citations
“…Although previous studies have analysed the relevance of demographic characteristics of prospective buyers of EVs [10,11,33], the findings of this literature are far from unanimous. Previous studies assert that demographic factors have a positive impact on both pro-environmental behaviour (e.g., [12,54] and in product innovation adoption [55].…”
Section: New Mobility Trendmentioning
confidence: 98%
“…To better understand the phenomenon, they used cluster analysis. Moreover, a cluster analysis is needed to uncover the similarity of citizens in terms of EV preferences [33]. Socio-demographic characteristics should be considered together.…”
Section: New Mobility Trendmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were obtained by Kumar and Alok [24], in their research, after an extensive overview of the literature, the team identified that income, higher level of education and multiple car ownership are all key elements that impact upon EV purchase. Others [25,26] have reported that young women with high income are more prone to purchase an EV. Opposite results are revealed by Sovacool et al [27], suggesting that men, with higher levels of education, having full-time employment, especially working in civil societies and academia, and below middle age (30e45), are the most likely to purchase an EV.…”
Section: Equity and Income Impacts On Ev Uptakementioning
confidence: 99%